Mechanism of abrupt supershear rupture for the 2021 Maduo earthquake (Mw=7.4) in the northern Tibetan Plateau - Wu, Kai; Zhu, Shoubiao; Huang, Jianping (Frontiers in Earth Science, 2025)
The 2021 Maduo earthquake (Mw = 7.4) is the first sudden and abrupt supershear rupture ever documented in the history of seismology, in which subshear rupture changed to supershear within a short time and short distance. However, the mechanism for this special phenomenon remains unclear although previous workers have done much work on it. For this reason, we use the finite element method to study the effects of fault geometry near the epicenter of the earthquake on the generation of rupture scenarios and use the grid-search approach to find the optimal model. Our simulation results show that the special fault geometry with a curved bend near the epicenter in the eastern segment of the fault induced supershear rupture transition at ∼3–5 s after the rupture nucleation, leading to the abrupt and sudden occurrence of the supershear rupture in the earthquake, whereas the westward-going rupture behaved as subshear in general. Additionally, the modeling results suggest that the co-seismic slips along the fault are mainly controlled by unevenly distributed dynamic friction coefficients. The modeling results also suggest that the other complex geometry of the fault, such as stepovers, cannot encourage the abrupt supershear rupture in the Maduo earthquake. Therefore, in this work, we may provide a new perspective for the study of the dynamic mechanism of supershear rupture.